Un modèle pour repenser l’éducation critique aux médias à l’ère du numérique - Pierre FASTREZ; Thibault PHILIPPETTE (Tic & Société)
Media education has always placed the development of critical thinking about media at the core of its project. In this article, we first discuss the definition of the adjective “critical” when applied to different objects (posture, pedagogy, situation and action). We then present a model of media literacy with which we explore the possible scope of a critical approach to media competencies in the context of digital media. In doing so, we propose a broader conception that connects technical, information and social perspectives on media, both in the context of their reception and their production, thereby extending beyond the traditional approach to media education, which restricts critical thinking to socio-informational reading skills.